Incision and aggradation in proglacial rivers: Post-Little Ice Age long-profile adjustments of Southern Iceland outwash plains - Roussel, Erwan; Marren, Philip; Cossart, Etienne; Toumazet, Jean-Pierre; Chenet, Marie; Grancher, Delphine; Jomelli, Vincent (Land Degradation & Development, 2018)
International audience The retreat of glaciers in response to climate warming leads to substantial changes in meltwater and sediment yield. Glacial shrinkage also induces the emergence and growth of proglacial margin landforms which strongly affect water and sedimentary transfers from the glacier to the outwash plains. On a decadal-timescale, field observations show that outwash plains of retreating glaciers typically exhibit proximal incision which decreases in magnitude downstream and stops at an inflection point where aggradation begins. Nevertheless, there is a lack of knowledge about the rates and magnitude of this fluvial adjustment and the effects of the proglacial margin configuration on the temperance or the aggravation of this fluvial adjustment to glacier retreat. This paper investigates the proglacial rivers of 14 retreating glaciers in southeast Iceland over a post-Little Ice Age timescale, combining fluvial deposits mapping, lichenometric dating and long-profile measurements of proglacial fluvial terraces. Our results demonstrate that: (1) proximal incision, associated with distal aggradation and downstream migration of the inflection point is the dominant pattern of proglacial river response to post-LIA glacier retreat in Iceland; (2) estimated mean rates of downstream migration of the inflection point range between 5 and 46 m.a-1 (3) the downstream migration rate of the inflection point is positively correlated with the proportion of proglacial lakes within the glacier foreland. These findings suggest that proglacial margins dominated by proglacial lakes intensify the rates of proximal incision and inflection point migration